Akreditasi sebagai Faktor Penentu dalam Keputusan Mahasiswa Masuk Perguruan Tinggi Muhammadiyah di Kalimantan Barat - Afriyanda, Fify; Samsuddin (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research Aim: This study analyzes the factors influencing students' decisions to choose universities, specifically Muhammadiyah universities in West Kalimantan. The focus is on the role of accreditation in shaping students' choices. Method: Using correlation and multiple regression analysis, the study investigates the relationship between University accreditation and students' enrollment decisions. Data were collected from 100 active students in their early semesters across three Muhammadiyah universities for the 2022/2023 academic year. Research Finding: The results reveal a significant correlation between accreditation and students' decisions, showing that students prioritize accreditation when selecting a University. Multiple regression analysis indicates that accreditation directly influences students' choices, explaining approximately 80.5% of the variation in their decisions. Theoretical Contribution: This research contributes to understanding how University accreditation is a critical factor in prospective student decision-making, adding to the body of knowledge on higher education marketing strategies. Practical Implication: The findings highlight the importance of University management in maintaining and improving its accreditation status to attract potential students. Institutions must also consider other factors such as reputation, tuition fees, location, facilities, and offered programs to create effective and sustainable student recruitment strategies. Research Limitation: The study is limited to three Muhammadiyah universities in West Kalimantan, which may affect the generalizability of the findings to other regions or institutions